Secondary prevention of myocardial infarction: effectiveness assessment in primary healthcare settings - Yu. I. Nesterov; S. A. Makarov; O. S. Krestova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To evaluate the effectiveness of ambulatory secondary prevention among patients after myocardial infarction (MI). Material and methods. In total, 208 ambulatory medical histories of patients, examined at the cardiology dispanser and three polyclinics, were analysed. All patients, aged 45-75 years, previously had an MI, with or without Q wave (1 month — 1 year ago). In addition, all patients underwent clinical interview. Results. A very low level of non-pharmaceutical therapy compliance was observed. Every fourth cardiology dispanser patient and every second polyclinic patient were not compliant to dietary recommendations; 47 % and 35,2 %, respectively, had low physical activity, and every second male patient was a current smoker. Cardiology dispanser and polyclinic doctors prescribed anti-aggregants to 86 % and 75 % of their patients, respectively. For beta-adrenoblockers, the respective percentages were 86 % and 52,8 %, and for statins — 87 % and 21,3 %. Lipid profile assessment was regularly performed in 49 % of the cardiology dispanser patients. In 11 %, lipid profile was assessed irregularly, and in 40 % of the cases, only total cholesterol level was measured. Conclusion. The study results suggest low compliance of primary healthcare patients to non-pharmaceutical therapy. Polyclinic doctors demonstrated inadequate knowledge on pharmacotherapy potential in treating postMI patients.